Food Consumption Behavior in Bandung Post COVID-19 Pandemic Emergence - Nugraha, Yosephine Carolina; Wissen, Sabrina; Kurniawan, Shafira Putri (Research Center and Case Clearing House PPM School of Management, 2024)
This research was done to discern changes in food consumption behavior in Indonesia two years after the emergence of the COVID-19 pandemic. Primary data for this research was gathered through questionnaires distributed from 26 June 2022 until 26 July 2022 to 258 respondents living in Bandung, Indonesia, using a simple random sampling method, which was then processed with SPSS. Results showed that people’s food consumption levels increased. Furthermore, changes in food consumption behavior are also identified, such as increased grocery and food purchases through online applications and increased cooking time. People also eat with their family more often, rather than eating out. The relatively more controlled COVID-19 situation also made people calmer and felt no need to stock up on foods with longer storage lives. This research faces a limitation regarding its respondents’ diversity. Follow-up research can be conducted to address the decrease in personal employees’ work level identified in this research